2021
DOI: 10.1097/cd9.0000000000000034
|View full text |Cite
|
Sign up to set email alerts
|

Normal-Weight Abdominal Obesity: A Risk Factor for Hypertension and Cardiometabolic Dysregulation

Abstract: Objective:This study aimed to examine the associations of waist circumference with hypertension and cardiometabolic dysregulation among normal-weight adults.Methods:This cross-sectional study included 8795 normal-weight participants aged 20 to 79 years from the 2009–2018 US National Health and Nutrition Examination Survey. The demographic characteristics and cardiometabolic risk factors across waist circumference quartiles were summarized. We used adjusted multivariate logistic regression models, subgroup anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…Interestingly, despite the consistent trend, no statistically significant association was observed in the subgroup of BMI > 28 kg/m 2 . Together with our previous results, 14 , 15 this study supported measuring and managing waist circumference regardless of BMI, which could provide additional opportunities to prevent obesity‐related cardiovascular events.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Interestingly, despite the consistent trend, no statistically significant association was observed in the subgroup of BMI > 28 kg/m 2 . Together with our previous results, 14 , 15 this study supported measuring and managing waist circumference regardless of BMI, which could provide additional opportunities to prevent obesity‐related cardiovascular events.…”
Section: Discussionsupporting
confidence: 84%
“…Accumulating studies have revealed the superiority of waist circumference in assessing the risk profiles related to abdominal fat distribution, 42–44 which contributes to the introduction of waist circumference in public health. Our recent cross‐sectional studies demonstrated that high waist circumference could elevate the prevalence of hypertension based on nationally representative US samples from the National Health and Nutrition Examination Survey 14,15 . In the US individuals, waist circumference was significantly associated with (pre) hypertension with adjusted odds ratios (95% CI) of 1.28 (1.18–1.40) in the young group and 1.23 (1.15–1.33) in the old group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, BMI-defined obesity is insufficient to fully capture the obesity-related metabolic risk. Previous studies have demonstrated that waist circumference is closely associated with multiple cardiovascular diseases and all-cause mortality independent of BMI ( 27 , 41 ). When evaluating obesity-related metabolic risk, these data supported that waist circumference and BMI were irreplaceable adiposity indexes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent consensus statement has highlighted the importance of routine measurement of waist circumference alongside BMI in classifying obesity and identifying individuals with high obesity‐related risk 10 . Also, our previous studies have revealed that waist circumference is positively and significantly associated with hypertension prevalence and cardiometabolic dysregulation regardless of BMI 11,12 …”
Section: Discussionmentioning
confidence: 99%